Novel candidate blood-based transcriptional biomarkers of Machado-Joseph disease - Raposo, Mafalda (2015)
BACKGROUND: Machado-Joseph disease (or spinocerebellar ataxia type 3) is a late-onset polyglutamine neurodegenerative disorder caused by a mutation in the ATXN3 gene, which encodes for the ubiquitously expressed protein ataxin-3. Previous studies on cell and animal models have suggested that mutated ataxin-3 is involved in transcriptional dysregulation. Starting with a whole-transcriptome profiling of peripheral blood samples from patients and controls, we aimed to confirm abnormal expression profiles in Machado-Joseph disease and to identify promising up-regulated genes as potential candidate biomarkers of disease status. METHODS: The Illumina Human V4-HT12 array was used to measure transcriptome-wide gene expression in peripheral blood samples from 12 patients and 12 controls. Technical validation and validation in an independent set of samples were performed by quantitative real-time polymerase chain reaction (PCR). RESULTS: Based on the results from the microarray, twenty six genes, found to be up-regulated in patients, were selected for technical validation by quantitative real-time PCR (validation rate of 81% for the up-regulation trend). Fourteen of these were further tested in an independent set of 42 patients and 35 controls; 10 genes maintained the up-regulation trend (FCGR3B, CSR2RA, CLC, TNFSF14, SLA, P2RY13, FPR2, SELPLG, YIPF6, and GPR96); FCGR3B, P2RY13, and SELPLG were significantly up-regulated in patients when compared with controls. CONCLUSIONS: Our findings support the hypothesis that mutated ataxin-3 is associated with transcription dysregulation, detectable in peripheral blood cells. Furthermore, this is the first report suggesting a pool of up-regulated genes in Machado-Joseph disease that may have the potential to be used for fine phenotyping of this disease.